Vers une culture du résultat. Dix étapes pour mettre en place un système de suivi et d'évaluation axé sur les résultats: Un guid pour les praticiens du développement = - Kusek, Jody Zall (Banque Mondiale, 2006)
An effective state is essential to achieving socio-economic and sustainable development. With the advent of globalization, there are growing pressures on governments and organizations around the world to be more responsive to the demands of internal and external stakeholders for good governance, accountability and transparency, greater development effectiveness, and delivery of tangible results. Governments, parliaments, citizens, the private sector, NGOs, civil society, international organizations and donors are among the stakeholders interested in better performance. As demands for greater accountability and real results have increased, there is an attendant need for enhanced results-based monitoring and evaluation of policies, programs, and projects. This Handbook provides a comprehensive ten-step model that will help guide development practitioners through the process of designing and building a results-based monitoring and evaluation system. These steps begin with a "Readiness Assessment" and take the practitioner through the design, management, and importantly, the sustainability of such systems. The Handbook describes each step in detail, the tasks needed to complete each one, and the tools available to help along the way.